Correlation between the growth of the Chinese aging rate and socioeconomic factors / Zhou Xiaoang and Doris Padmini Selvaratnam - Zhou, Xiaoang; Selvaratnam, Doris Padmini (Universiti Teknologi MARA, Cawangan Melaka, 2023)
This study examines the impact of various socioeconomic factors on population aging in China over the period 1978-2019. An ordinary least square regression model is utilized to analyze the relationship between aging rates and socioeconomic variables such as GDP, CPI, urbanization rate, unemployment rate, and family planning policy. The findings reveal positive correlations between GDP, CPI, urbanization rate, and family planning policy with China's aging rate. Consequently, effective strategies to address population aging should prioritize the quality of economic development through structural reforms, prudent fiscal and monetary policies, and bolstered support for social welfare programs. Targeted adjustments to current family planning policies are crucial in stimulating higher birth rates and supporting larger families. Moreover, refocusing development efforts on small and medium-sized cities and rural areas will help address the implications of rapid urbanization on the pace of aging. This study enhances the understanding of socioeconomic factors impacting the aging rate in China, offering valuable insights to policymakers in formulating more effective strategies. By considering the diverse socioeconomic aspects, policymakers can better prepare for and respond to the challenges presented by population aging.